ANALISA FAKTOR-FAKTOR PENYEBAB KEMATIAN BAYI DENGAN ASFIKSIA DI KABUPATEN SEMARANG TAHUN 2012 - Joyo Minardo; Kartika Sari; Tutik Susilowati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Asphyxia neonatorum is a condition in which the baby can not breathe spontaneously and regularly soon after birth due to several factors: maternal factors, factors from the placenta, fetal factors, factors of labor, and of multifactorial. This study aims to investigate the characteristics of mothers with infants died of asphyxia in Semarang district in 2012 andanalyzes the factors that cause infant death due to asphyxia in Semarang district in 2012. This research is a retrospective study using cross-sectional approach . Subjects were mothers with infants died of asphyxia in Semarang Regency in 2012 , time studies in January 2014. Theresearch instrument using the checklist and perinatal mortality audit records . Technical analysis of the data using univariate analysis. Based on the research that the characteristics of pregnant women who have a baby die of asphyxia mostly aged between 20-35 years of age productive oras many as 29 ( 76 % ) of people , berparitas < 4 which is 36 people ( 95 % ) , junior high school education is 21 people ( 55 % ) , age at term pregnancy is 28 people ( 74 % ) . The results showed 13 infants ( 34.2 % ) died due to asphyxia with the causes of fetal factors , 13 infants ( 34.2 % ) died due to asphyxia with the cause of multi- factor , 10 infants ( 26.3 % ) died due to asphyxia with a cause of the labor factor 2 infants ( 5 % ) died due to asphyxia with the causes of maternal factors , not the baby died because of asphyxia obtained with the causes of placental factors . Advice given is a health worker should be more thorough in examiningpregnant women and more prudent in taking actions that can overcome the disstres fetal asphyxia not allow to happen.